2021
DOI: 10.3389/fimmu.2021.760708
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Severe Infections Following Rituximab Administration in Patients With Autoimmune Kidney Diseases: Austrian ABCDE Registry Analysis

Abstract: ObjectiveTo characterize the incidence, type, and risk factors of severe infections (SI) in patients with autoimmune kidney diseases treated with rituximab (RTX).MethodsWe conducted a multicenter retrospective cohort study of adult patients with immune-related kidney diseases treated with at least one course of RTX between 2015 and 2019. As a part of the ABCDE Registry, detailed data on RTX application and SI were collected. SI were defined by Common Terminology Criteria for Adverse Events v5.0 as infectious c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
(20 reference statements)
1
12
0
2
Order By: Relevance
“…Our results suggested that respiratory infection and Gram-negative bacterial and fungal infection during the first 3 months were independently associated with 1-year mortality. Respiratory infection in AAV, as the most common infection type, is almost unanimous in all studies 4–7 10 16 18 19 25–28. Due to the fact that patients with AAV often exhibit pulmonary involvement at the onset, which presents as interalveolar haemorrhage, the function of the endothelium is possibly damaged.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggested that respiratory infection and Gram-negative bacterial and fungal infection during the first 3 months were independently associated with 1-year mortality. Respiratory infection in AAV, as the most common infection type, is almost unanimous in all studies 4–7 10 16 18 19 25–28. Due to the fact that patients with AAV often exhibit pulmonary involvement at the onset, which presents as interalveolar haemorrhage, the function of the endothelium is possibly damaged.…”
Section: Discussionmentioning
confidence: 99%
“…or cyclophosphamide (CYC)), have been identified as risk factors for infection in patients with AAV. [5][6][7][8][9][10][11][12][13][14][15] These factors are intertwined, which places clinicians in a therapeutic dilemma. A better understanding of infection-related factors helps to balance the benefits and risks associated with treatment.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as rituximab therapy is concerned, a considerable percentage of patients with AAV may be susceptible to severe infections, with increasing age, impaired renal function, and lower body mass index acting as risk factors [90,91]. Dosing regimens (four-dose and two-dose) do not differ in the rate of incident infections [92].…”
Section: Immunosuppressive Agents and Infections In Vasculitidesmentioning
confidence: 99%
“…По данным ретроспективного совместного исследования, выполненного в ревматологических центрах Швеции и Мексики, частота тяжелых КИ у больных АНЦА-СВ, получавших РТМ, составила 24% [39]. К факторам риска КИ при лечении РТМ относят увеличение возраста, нарушение функции почек и снижение массы тела [39,40]. Недавно опубликованные результаты байесовского метаанализа РКИ показали, что микофенолата мофетил был, по всей вероятности, наиболее безопасным препаратом в отношении КИ у больных АНЦА-СВ, далее следовали ЦФ, азатиоприн, РТМ и метотрексат [41].…”
Section: инфекция как осложнение свunclassified